Assessment of the impact of Charter Party clauses and port's characteristics on the port's financial result. (February 2019) - Mazioli, Franco Collodetti; Rosa, Rodrigo de Alvarenga; Sagrilo, Ricardo Gottardi Ventura; Vitorugo, Lirielly Ruela; Neves, Bruna dos Santos
Highlights: The impact of Charter Party clauses on the port's financial result is assessed. The impact of the port's characteristics on the port's financial result is assessed. 300 instances based on a real case of a specialized port in general cargo are tested. The shipper owns a port to operate its cargo and the ships are contracted under Charter Party contracts. A mathematical model and a metaheuristic are proposed to solve the problem. Abstract: Some ports belong to one single shipper, which plans the port operation according to the affreightment contract with the shipowner, known as Charter Party. Therefore, it is important to plan the port operation based on the Charter Party, mainly considering dispatch and demurrage, to achieve a better financial result to the port. This paper proposes a mathematical model and a metaheuristic to plan the port operation, considering dispatch and demurrage, aiming to increase the dispatch received and to reduce the demurrage paid by the shipper, which is the owner of the port. We tested 300 instances based on the major Brazilian wood pulp port, aiming to assess the impact of Charter Party clauses (layday, laytime, dispatch and demurrage) and port's characteristics (quay's length and operation time) in the port's financial result. Results show that layday, demurrage and quay's length had higher negative impact on the port's financial result than the other assessed parameters.